Clinical analysis of 25 cases of infant umbilical granuloma treated with topical application of common salt granules - Bao, Jingfeng; Li, Hailin; Yu, Donghai; Jiang, Ling; Hong, Yaqiang (Frontiers in Pediatrics, 2025)
ObjectiveTo summarize our experience with topical application of common salt granules for the treatment of infant umbilical granuloma and to evaluate its clinical value.MethodsA retrospective analysis was conducted on 25 cases of umbilical granuloma treated with common salt granules from January 2024 to June 2024.ResultsAll 25 cases were successfully treated, with a mean treatment duration of 2.5 days (range: 1.5–9 days). The cure rate was 100%, with no recurrence or complications observed during a 3-month follow-up.ConclusionTopical application of common salt granules appears to be a simple, effective, safe, and cost-effective treatment for infant umbilical granuloma, based on our retrospective analysis. Further studies are needed to confirm these findings.